Core needle biopsies and surgical excision biopsies in the diagnosis of lymphoma: experience at the Lymph Node Registry Kiel - Johl, Alice; Lengfelder, Eva (Annals of hematology, 2016)
Current guidelines of the European Society of Medical Oncology recommend surgical excision biopsies of lymph nodes for the diagnosis of lymphoma whenever possible. However, core needle biopsies are increasingly used. We aimed to understand the common practice to choose the method of biopsy in Germany. Furthermore, we wanted to understand performance of surgical excision and core needle biopsies of lymph nodes in the diagnosis of lymphoma. The files of 1510 unselected, consecutive lymph node specimens from a consultation center for lymphoma diagnosis were analyzed. Core needle biopsies were obtained frequently from lymph nodes localized in mediastinal, abdominal, retroperitoneal, or thoracic regions. Patients undergoing core needle biopsies were significantly older and suffered significantly more often from lymphoma than patients undergoing surgical excision biopsies. Although more immunohistochemical tests were ordered by the pathologist for core needle biopsies specimens than for surgical excision biopsies specimens, core needle biopsies did not yield a definite diagnosis in 8.3 % of cases, compared to 2.8 % for SEB (p = 0.0003). Restricting the analysis to cases with a final diagnosis of follicular lymphoma or diffuse large B-cell lymphoma, core needle biopsies identified a simultaneous low- and high-grade lymphoma (transformation) in 3.3 % of cases, compared to 7.6 % for surgical excision biopsies (p = 0.2317). In Germany, core needle biopsies are preferentially used in elderly patients with a high likelihood of suffering from lymphoma. Core needle appeared inferior to surgical excision biopsies at providing a definite diagnosis and at identifying multiple lymphoma differentiations and transformation.